First measurements with a plastic scintillation dosimeter at the Australian MRI-LINAC. (4th September 2019) - Madden, Levi; Archer, James; Li, Enbang; Jelen, Urszula; Dong, Bin; Roberts, Natalia; Holloway, Lois; Rosenfeld, Anatoly
Abstract: MRI-LINACs combine MRI and LINAC technologies with the potential for image guided radiation therapy with optimal soft-tissue contrast. In this work, we present the advantages and limitations of plastic scintillation dosimeters (PSDs) for relative dosimetry with MRI-LINACs. PSDs possess many desirable qualities, including magnetic field insensitivity and irradiation angle independence, which are expected to make them suitable for dosimetry with MRI-LINACs. An in-house PSD was used to measure field size output factors as well as a percent depth dose distribution and the beam quality index TPR20/10 at a cm 2 field size. Measurements were repeated with a Scanditronix/Wellhofer FC65-G ionisation chamber and PTW 60019 microDiamond detector for comparison. Relative differences were calculated between the three detectors, where the mean difference in dose was 1.2% between the PSD and ionisation chamber, 1.9% between the PSD and microDiamond detector and 1.3% between the microDiamond detector and the ionisation chamber. The closeness between the three mean differences in doses suggests that PSDs are feasible for relative dosimetry with MRI-LINACs.